Epidemiology of dermatomycoses in 30 years of study at Daniel a Carrion Institute of Tropical Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru - Béjar, Vilma (2014)
Objectives: To determine dermatomycoses epidemiological evolution in outpatients during the period 1976-2005. Design: Descriptive, retrospective, and analytical study. Setting: Daniel Alcides Carrion Institute of Tropical Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Patients positive to dermatomycoses. Interventions: Medical records of 7 185 (55.3%) dermatomycoses-positive patients were reviewed. Main outcome measures: Etiologic agent, season, gender, age, and clinical forms. Results: Females (52.1%) and the 16 to 30 year-old group (42.7%) were the most affected. Most frequent dermatomycoses was onychomycosis (43.6%). Most prevalent pathogens were Trichophyton rubrum (33.2%), Candida albicans (15.3%), Candida non albicans (11.8%), Trichophyton mentagrophytes (9.4%), Malassezia spp. (9.1%), and mixed infections (7.2%). The fungal scalp infection showed steady increase during the period studied. Epidermophyton floccosum dermatophyte was isolated for the last time in the 1990s. Since 1995 prevalence of Candida non albicans has increased and Candida tropicalis yeast species are re-emerging. Conclusions: Epidemiological changes in dermatomycoses clinical forms and etiology were found between 1976 and 2005.